Relationship between Gastroesophageal Reflux Disease (GERD) with Quality of Sleep - Ginting, Elianora Bergita; Darmadi; Sofyan, Ferryan; Kaban, Sri Melinda (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2024)
Background. Gastroesophageal Reflux Disease (GERD) is a common gastrointestinal disorder caused by reflux of stomach contents into the esophagus, as a result, it causes various symptoms or complications . GERD is a commonly prevalent gastrointestinal disorder in medical students. Based on data from the 2006 US National Health and Wellness survey observing respondents who experienced heartburn at least twice a month, 89% of respondents experiencing nightime GERD symptoms, it showed that the presence of nighttime GERD was associated with decrease quality of sleep. This study aimed to analyze the relationship between GERD and students’ sleep quality in Faculty of Medicine USU 2020-2022. Method. Cross sectional design with total sampling method. Data collection was carried out using an online questionnaire in the form of a google form. The questionnaires used were GERD-Q, FSSG, PSQI, and ISI. The analysis used was univariate and bivariate analysis with Chi-square. Results. This study involved 378 respondents, 114 people (30.2%) with GERD, 67 people (58.8%) with severe of GERD, 286 people (75.7%) had a bad quality of sleep, and 43 people (15%) with moderate and severe of insomnia. The results of statistical analysis showed an association between GERD and quality of sleep. Conclusion. There was a correlation between GERD and quality of sleep of USU Faculty of Medicine students class 2020-2022